O Comando de Caça aos Comunistas (CCC): do estudante ao terrorista (1963-1980) - Lima, Danielle Barreto (2020)
This work aims to research the Communist Hunt Command (CCC), especially its actions and guidelines, during the period of the civil-military dictatorship, with a focus on its work from 1963 to 1980, its methods of action and social and political aspirations. Considering the few researches on the performance of so-called "conservative" students, or at the time called "democratic", during the dictatorship, especially regarding students who were part of conservative and reactionary groups, the intention is to identify and analyze the practices and ideology of this group, which was marked by its paramilitary action and favorable to the political closure of the Brazilian dictatorial regime. For this purpose, various types of documentation produced at the time, such as those from the repressive apparatus, the press and the student movement, found in different digital archives and repositories, were analyzed. For the research, the idea of "anti-communism" is understood as an industry that generates an imaginary fear, starting with the work of Motta (2000). The CCC organized itself in 1963 and acted within the political-university environment, within university action networks, as a mobilization of the right, from parties and statutory academic centers, formed by students from the Law School of the University of São Paulo and the Mackenzie Presbyterian University. Since 1968, the acronym has been used in acts in other parts of the country, by groups which, although it could not be said to be directly guided by the CCC that emerged in São Paulo, resembled the practice of violence and persecution of those who dared to oppose the regime. The acts attributed to the group go back to the 1970s and 1980s, becoming more present during the process of democratic reopening. The CCC's performance within the repressive apparatus, especially after the decree of AI-5, is also analyzed, with emphasis on the human rights violations committed during the dictatorship and the impunity guaranteed to the group and its members since its creation